Dealing with Informality in Water Supply Services in Indonesia - Setiawan, Deviariandy (World Bank, Washington, DC, 2012)
Communities demand that community-based water provider organizations (CBOs) be more professional in their delivery of water and provide the level of service they expect. This demand may be a challenge, not only in terms of the internal capacity of the CBO but also in terms of the uncertainty as to the legal status of the organization that performs the service function. A dearth of corporate practice, efforts toward formalization, accountability framework, and partnership definition are areas that policymakers and local authorities need to work on if they want CBOs to perform their role better in water supply, particularly in rural areas. This smart lesson describes the Multi Village Pooling Project's experience in generating lessons on the challenges and potential of CBOs formed under previous projects and identifies ways to help them improve, expand, and manage on a continuing basis.